Improving Service Excellence in the Procurement Process of Products Through the HaloProc Chatbot: A Project at XYZ - Purwoko, Harry; Budiman, Tenaka; Harsoyo, Tri (Siber Nusantara Review & Yayasan Sinergi Inovasi Bersama (SIBER), 2025)
The procurement department plays a very important role in XYZ's operational continuity. The procurement team faces several challenges, such as complex and lengthy processes, limited communication, time, and resources, the length of time it takes for service users to take care of procurement documents, and understated budget absorption. This research aims to find the cause of these problems and provide solutions. This study uses qualitative methods by using a root cause analysis or cause-and-effect analysis worked by the procurement team. The results of the cause-and-effect analysis were combined with the Five Quality and Risk Matrix method. The result was the finding that the quality factor of procurement preparation was the most important root cause with a Risk Level of 15 or 41.67% of all root problems, mainly due to the lack of proper means of communication between the service user and the procurement team. Several solutions were proposed, and the one agreed upon was to create a booking system using a ChatBot called HaloProc. The implementation of HaloProc most likely will help improve service excellence in the procurement process of XYZ.